Carbon nanotube modified carbon black conductive powder as well as preparation method and application thereof
By growing nitrogen-containing carbon nanotubes in situ on the surface of carbon black, the carbon nanotube modified carbon black conductive powder is solved, and the existing conductive agent has poor conductivity, high carbon black addition amount and complex process are achieved, and high conductivity is achieved , low carbon black usage and simplified process effects.
Patent Information
- Application Number
- CN202411377211.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-11
AI Technical Summary
The existing conductive agents used in lithium-ion batteries have problems such as poor conductivity, high carbon black addition and complex process.
Carbon nanotube modified carbon black conductive powder is used to grow nitrogen-containing carbon nanotubes in situ on the surface of the carbon black to form a chemical combination between carbon black and carbon nanotubes, thereby improving conductivity.
It realizes a conductive agent with good conductivity, reduces the amount of carbon black, simplifies the process, and improves the capacity and rate performance of lithium-ion batteries.
Smart Images

Figure CN119419270A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of material technology, and specifically relates to a carbon nanotube-modified carbon black conductive powder and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have broad application prospects in portable electronic devices and electric vehicles due to their high operating voltage, large specific capacity, stable discharge, small size, light weight, no memory effect, high safety, long life and environmental friendliness. Conductive agents are often used in the positive and negative pole pieces of lithium-ion batteries. Conductive agents can improve the activity of pole piece materials, thereby improving the performance of lithium-ion batteries.
[0003] Conductive agents commonly used in lithium-ion batteries include conductive carbon black, carbon nanotubes and graphene. Among them, conductive carbon black can be added to the pole piece material in the form of powder, and the process is simple and easy to operate, but the conductivity of conductive carbon black is poor, and a low addition amount will lead to a low capacity of the lithium-ion battery, so a high addition amount is required; while carbon nanotubes have good conductivity, a low addition amount, and can also improve the capacity and rate performance of lithium-ion batteries, but they need to be added to the pole piece material in the form of slurry, and the process is very complicated.
[0004] Therefore, it is necessary to provide a conductive agent with good conductivity, low carbon black addition and simple process. Summary of the invention
[0005] The purpose of the present application is to overcome the above-mentioned deficiencies of the prior art and to provide a carbon nanotube-modified carbon black conductive powder and a preparation method and application thereof, so as to solve the problems of poor conductivity, high carbon black addition amount and complex process of the existing conductive agents used in lithium-ion batteries.
[0006] In order to achieve the above application purpose, the first aspect of the present application provides a carbon nanotube-modified carbon black conductive powder, comprising: carbon black and nitrogen-containing carbon nanotubes, wherein the nitrogen-containing carbon nanotubes are in-situ grown on the surface of the carbon black; the weight ratio of the carbon black to the nitrogen-containing carbon nanotubes is in the range of 10:1-3:1;
[0007] The oil absorption range of the carbon nanotube modified carbon black conductive powder is 210-280 ml / 100 g;
[0008] and / or,
[0009] The resistivity of the carbon nanotube-modified carbon black conductive powder is in the range of 50-90 mΩ·cm;
[0010] and / or,
[0011] The specific surface area of the carbon nanotube modified carbon black conductive powder is in the range of 110-180 m 2 / g.
[0012] Furthermore, the carbon nanotube-modified carbon black conductive powder is obtained by the following steps:
[0013] Step 1. Carbon black supports metal catalyst;
[0014] Step 2. In-situ growth of carbon nanotubes on the surface of the carbon black loaded with the metal catalyst and treatment to form the carbon nanotube-modified carbon black conductive powder;
[0015] The in-situ growth of carbon nanotubes on the surface of carbon black loaded with a metal catalyst is carried out in two stages: in the first stage, the carbon black loaded with a metal catalyst is reacted at a fourth temperature for a fourth time in a carbon source at a first gas flow rate, a nitrogen source at a second gas flow rate, and a fourth protective gas at a third gas flow rate; the second stage is: reacting at a fifth temperature for a fifth time in a carbon source at a fourth gas flow rate, a nitrogen source at a fifth gas flow rate, and a fifth protective gas at a sixth gas flow rate to form a composite powder with nitrogen-containing carbon nanotubes in situ grown on the surface of the carbon black; wherein the first gas flow rate is less than the fourth gas flow rate, the second gas flow rate is greater than the fifth gas flow rate, and the fourth temperature is greater than the fifth temperature.
[0016] Furthermore, after the step 1. of loading the metal catalyst on the carbon black and before the step 2. of in-situ growing carbon nanotubes on the surface of the carbon black loaded with the metal catalyst and treating the carbon nanotubes to form the carbon nanotube-modified carbon black conductive powder, the following steps are also included:
[0017] Step 1.5. Activating the metal catalyst;
[0018] The activation treatment of the metal catalyst includes: reducing the carbon black and carbon nanotubes loaded with the metal catalyst in hydrogen and nitrogen with a gas flow rate range of 100-150 L / min and a temperature of 600-700° C. for 5-10 minutes to form an activated carbon black loaded metal catalyst; wherein hydrogen is used as a reducing gas and nitrogen is used as a protective gas.
[0019] Furthermore, the volume ratio of hydrogen to nitrogen is in the range of 1:1-2:1.
[0020] Furthermore, the in-situ growth of carbon nanotubes on the surface of carbon black loaded with a metal catalyst is carried out in two stages: in the first stage, the carbon black loaded with a metal catalyst is reacted in a carbon source with a first gas flow rate, a nitrogen source with a second gas flow rate, and a fourth protective gas with a third gas flow rate at a fourth temperature for a fourth time; in the second stage, the carbon source with a fourth gas flow rate, a nitrogen source with a fifth gas flow rate, and a fifth protective gas with a sixth gas flow rate are reacted at a fifth temperature for a fifth time to form a composite powder with nitrogen-containing carbon nanotubes in-situ grown on the surface of carbon black, including:
[0021] The activated carbon black loaded with a metal catalyst is transported to a reaction furnace by a first inert gas. In the first stage, a carbon source with a gas flow rate in the range of 400-500 L / min, a nitrogen source with a gas flow rate in the range of 80-150 L / min, and a second inert gas with a gas flow rate in the range of 550-650 L / min are used to react at a temperature of 660-700°C for 8-15 minutes. In the second stage, a carbon source with a gas flow rate in the range of 500-600 L / min, a nitrogen source with a gas flow rate in the range of 30-50 L / min, and a third inert gas with a gas flow rate in the range of 550-650 L / min are used to react at a temperature range of 600-650°C for 30-40 minutes to obtain a composite powder with nitrogen-containing carbon nanotubes in situ grown on the surface of the carbon black.
[0022] Furthermore, the steps of loading the metal catalyst with carbon black are as follows:
[0023] The conductive carbon black is subjected to acid treatment and drying to obtain the carbon black subjected to acid purification;
[0024] The metal salt solution, the carbon black purified by the acid solution and the complexing agent are mixed and treated to obtain the carbon black loaded with the metal catalyst.
[0025] Furthermore, the step of acidifying and drying the conductive carbon black to obtain the acid-purified carbon black comprises:
[0026] Conductive carbon black with a powder particle size range of 100-20000nm and a resistivity range of 0.2-50Ω·cm is placed in an acid solution with a molar concentration range of 0.7-1.2mol / L, pretreated at a temperature of 70-100°C for 1-3h, filtered and washed until the filtrate is neutral, and then dried at a temperature of 110-130°C for 19-24h to obtain the carbon black purified by the acid solution.
[0027] Furthermore, the metal salt solution, the carbon black purified by the acid solution and the complexing agent are mixed and treated to obtain the carbon black loaded with the metal catalyst, which comprises:
[0028] The metal salt solution, the carbon black purified by the acid solution and the complexing agent are mixed, heated to 100-300°C, maintained at a pressure of 0.1-0.4MPa, and immersed for 0.5-3h to obtain a catalyst precursor, and then the catalyst precursor is placed in a muffle furnace, calcined for 2-7h in a first protective atmosphere at a temperature of 450-620°C, and sieved with a sieve of 80-100 mesh after cooling to obtain the carbon black loaded with the metal catalyst.
[0029] Furthermore, the weight ratio of the carbon black purified by acid solution, the complexing agent, and the metal salt in the metal salt solution is in the range of 1.2-1.5:1.05-1.2:0.8-1.2.
[0030] In a second aspect of the present application, a lithium-ion battery is provided, comprising the above-mentioned carbon nanotube-modified carbon black conductive powder.
[0031] Compared with the prior art, this application has the following technical effects:
[0032] The carbon nanotube-modified carbon black conductive powder and its preparation method and application provided in the embodiments of the present application adopt high-temperature pressure impregnation to load the carbon black with a metal catalyst. The high temperature and pressure of this process accelerate the diffusion rate of the active component, so that the metal catalyst is evenly dispersed on the surface of the carbon black, and the loading amount and uniformity of the metal catalyst loaded on the carbon black are improved; at the same time, the metal catalyst in the carbon black loaded with the metal catalyst is calcined and then subjected to reduction activation treatment, which can enhance the catalytic activity of the metal catalyst and is beneficial to the subsequent generation of carbon nanotubes; and, carbon nanotubes are generated in multiple stages in a reactor, so that a nitrogen source can be inserted into defects in the carbon hexagonal ring and other locations, and nitrogen-containing carbon nanotubes can be grown in situ on the surface of the carbon black, thereby achieving chemical bonding between the carbon black and the carbon nanotubes and enhancing the conductivity of the carbon nanotube-modified carbon black high-conductivity powder.
[0033] When carbon nanotube-modified carbon black high-conductivity powder is used as a conductive agent, a conductive path can be obtained when using a small amount. In particular, the nitrogen source also improves the conductivity, which inevitably reduces the amount of carbon black used. When it is used as a conductive agent, it can be directly added to the system in the form of powder, which is very easy to disperse into various systems and is simple and easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0035] Figure 1 is a process flow chart of a carbon black-supported metal catalyst provided in an embodiment of the present application;
[0036] Figure 2 This is a process flow chart for preparing a carbon nanotube-modified carbon black conductive powder provided in an embodiment of the present application. DETAILED DESCRIPTION
[0037] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0038] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0039] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all mean: a, b, c, ab (i.e. a and b), ac, bc or abc, where a, b, c can be single or multiple, respectively.
[0040] It should be understood that in the various embodiments of the present application, the size of the serial number of each process does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0041] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0042] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass in the embodiment description of the present application can be a well-known mass unit such as μg, mg, g, kg, etc.
[0043] The terms "first", "second", etc. are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, a feature defined as "first", "second", etc. may explicitly or implicitly include one or more of the features.
[0044] In a first aspect, an embodiment of the present application provides a method for preparing carbon nanotube-modified carbon black conductive powder.
[0045] First, if Figure 1 As shown, the present embodiment provides a step of carbon black loading metal catalyst:
[0046] S11. Select conductive carbon black, place the conductive carbon black in an acid solution, treat it at a pretreatment temperature for a first time, filter and wash until the filtrate is neutral, and dry it to obtain carbon black purified by the acid solution.
[0047] In applications, the conductive carbon black may be N326 or the like.
[0048] The particle size of the conductive carbon black powder may range from 100 to 20000 nm.
[0049] The resistivity of the conductive carbon black may be in the range of 0.2-50Ω·cm. For example, the resistivity of the conductive carbon black may be 0.2Ω·cm, 1Ω·cm, 10Ω·cm, 20Ω·cm, 30Ω·cm or 50Ω·cm.
[0050] The acid solution may include hydrochloric acid (HCl), sulfuric acid (H 2 SO 4 ) and nitric acid (H 3 PO 4 ) and the like. Preferably the acid solution is concentrated HCl, concentrated H 2 SO 4 He Cong H 3 PO 4 A combination of one or more of the following, wherein concentrated HCl refers to a hydrochloric acid solution with a mass fraction of HCl exceeding 20%. 2 SO 4 It means H 2 SO 4 The mass fraction of sulfuric acid is greater than or equal to 70%, and the concentrated H 3 PO 4 Generally refers to H 3 PO 4 Nitric acid solution above 8 mol / L.
[0051] The molar concentration of the acid solution may range from 0.7 to 1.2 mol / L. For example, the molar concentration of the acid solution may be 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L or 1.2 mol / L, etc. Preferably, the molar concentration of the acid solution is 1.0 mol / L.
[0052] The pretreatment temperature range may be 70-100°C, the first time range may be 1-3h, for example, the pretreatment temperature may be 70°C, 80°C, 85°C, 90°C, 95°C or 100°C, etc., and the first time may be 1h, 1.5h, 2h, 2.5h, 2.8h or 3h, etc. Preferably, the pretreatment temperature is 90°C, and the first time is 2h.
[0053] The drying temperature may range from 110 to 130°C, and the drying time may range from 19 to 24 hours. For example, the drying temperature may be 110°C, 115°C, 120°C, 123°C, 128°C or 130°C, and the drying time may be 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, etc. Preferably, the drying temperature is 120°C, and the drying time is 24 hours.
[0054] Acid treatment can remove metal impurities, ash, etc. of conductive carbon black, increase the surface functional groups and defects of conductive carbon black, and improve the dispersibility of conductive carbon black. At the same time, acid treatment can increase the active sites on the surface of conductive carbon black, making it easier for the metal salt in the metal salt solution in the subsequent step to be adsorbed on the surface of conductive carbon black purified by acid under the action of the complexing agent.
[0055] S12. Prepare a metal salt solution.
[0056] In applications, the metal salt solution may include a combination of one or more of a nitrate solution, a hydrochloride solution, and a sulfate solution, and the metal salt in the metal salt solution may include a combination of one or more of an iron (Fe) salt, a cobalt (Co) salt, an iron-cobalt salt, and a nickel (Ni) salt. Exemplary, the metal salt solution may include iron nitrate (Fe(NO 3 ) 3 ) solution, ferrous chloride (FeCl 2 ) solution, ferric chloride (FeCl 3 ) solution, ferrous sulfate (Fe 2 (SO 4 ) 3 ) solution, cobalt nitrate (Co(NO 3 ) 2 ) solution, cobalt chloride (CoCl 2 ) solution, cobalt sulfate (CoSO 4) solution, nickel nitrate (Ni(NO 3 ) 2 ) solution, nickel chloride (NiCl 2 ) solution, nickel sulfate (NiSO 4 ) solution and cobalt ferrite (Co 2 Fe 2 O 5 )wait.
[0057] When the metal salt solution contains Fe, Co and Ni at the same time, the Fe salt can be used as the main catalyst, the Co salt can be used as the auxiliary catalyst, and the Ni salt can be used as the auxiliary agent. The molar ratio of Fe, Co and Ni can range from 0.7-1.2:0.7-1.2:0.3-0.8. For example, the molar ratio of Fe, Co and Ni can be 0.7:0.7:0.3, 0.8:0.8:0.4, 0.9:0.9:0.5, 1:1:0.6, 1.1:1.1:0.7 or 1.2:1.2:0.8, etc. Preferably, the molar ratio of Fe, Co and Ni is 1:1:0.6.
[0058] It should be noted that there is no specific limitation on the order of the above steps S11 and S12. Step S11 may be performed first, and then step S12; or, step S12 may be performed first, and then step S11; or, step S11 and step S12 may be performed simultaneously.
[0059] S13. After uniformly mixing the metal salt solution, the carbon black purified by the acid solution and the complexing agent, heat to the first temperature, and immerse under the first pressure for a second time to obtain a catalyst precursor, and then place the catalyst precursor in an atmosphere of the first protective gas and roast at the second temperature for a third time, cool and sieve to obtain carbon black loaded with a metal catalyst.
[0060] In application, the complexing agent may include one or more combinations of citric acid, tartaric acid, sorbic acid, ethylenediaminetetraacetic acid, ethylene glycol, polyethylene glycol, glycerol, and the like.
[0061] The weight ratio of the carbon black, complexing agent, and metal salt in the acid-purified solution can be in the range of 1.2-1.5:1.05-1.2:0.8-1.2. For example, the weight ratio of the carbon black, complexing agent, and metal salt in the acid-purified solution can be 1.2:1.05:0.8, 1.25:1.08:0.9, 1.3:1.1:1.0, 1.35:1.15:1.0, 1.4:1.18:1.1, or 1.5:1.2:1.2, etc. Thus, the precipitation rate and particle size of the metal salt can be adjusted so that it can be uniformly precipitated on the surface of the carbon black.
[0062] The first temperature may be in the range of 100-300°C. For example, the first temperature may be 100°C, 150°C, 200°C, 250°C, 280°C or 300°C, etc. Preferably, the first temperature is 200°C.
[0063] The first pressure may range from 0.1 to 0.4 MPa. For example, the first pressure may be 0.1 MPa, 0.15 MPa, 0.2 MPa, 0.25 MPa, 0.3 MPa or 0.4 MPa, etc. Preferably, the first pressure is 0.2 MPa.
[0064] The second time range may be 0.5-3 hours, and illustratively, the second temperature may be 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours, etc. Preferably, the second time is 2 hours.
[0065] The catalyst precursor may be placed in a muffle furnace for calcination.
[0066] The first protective atmosphere may be an inert gas atmosphere, and the inert gas may be nitrogen (N 2 ), helium (He), neon (Ne) and argon (Ar), etc.
[0067] The second temperature may be in the range of 450-620°C. For example, the second temperature may be 450°C, 480°C, 500°C, 550°C, 580°C or 620°C.
[0068] The third time range may be 2-7 hours, and illustratively, the third time may be 2 hours, 3 hours, 4 hours, 5 hours, 6 hours or 7 hours, etc. Preferably, the third time is 4 hours.
[0069] The sieve may be used for sieving, and the mesh number of the sieve may range from 80 to 100 meshes. For example, the mesh number of the sieve may be 80 meshes, 85 meshes, 90 meshes, 95 meshes, 98 meshes or 100 meshes, etc.
[0070] The carbon black purified by acid solution can be used as a carrier and has an adsorption effect, so it can well load the metal salt in the metal salt solution and adsorb the complex formed by the metal salt and the chelating agent. On this basis, the carbon black loaded with the metal catalyst is subjected to high-temperature pressure impregnation and other treatments to make the metal catalyst evenly dispersed on the surface of the carbon black, thereby improving the loading amount and uniformity of the metal catalyst loaded on the carbon black.
[0071] The specific steps of carbon black loaded metal catalyst are given below:
[0072] (1). Selection and pretreatment of carbon black:
[0073] Conductive carbon black with a powder particle size of 100-20000nm and a resistivity of 0.2-50Ω·cm is selected, the conductive carbon black is placed in an acid solution with a molar concentration of 0.7-1.2mol / L, pretreated at 70-100°C for 1-3h, filtered and washed until the filtrate is neutral, and then dried at 110-130°C for 19-24h to obtain carbon black purified by acid solution.
[0074] (2) Prepare metal salt solution.
[0075] (3). Carbon black loaded metal catalyst:
[0076] The metal salt solution, the carbon black purified by acid solution and the complexing agent are mixed in water (H 2 O) are mixed uniformly, heated to 100-300° C., maintained at a pressure of 0.1-0.4 MPa, and impregnated for 0.5-3 h to obtain a catalyst precursor, and then the catalyst precursor is placed in a muffle furnace, calcined at a first protective atmosphere and 450-620° C. for 2-7 h, and sieved with a 80-100 mesh sieve after cooling to obtain carbon black loaded with a metal catalyst.
[0077] Then, if Figure 2 As shown, the embodiment of the present application provides a method for preparing carbon nanotube-modified carbon black conductive powder, comprising the following steps:
[0078] S21. Under the atmosphere of the second protective gas and the reducing gas, the metal catalyst in the carbon black loaded with the metal catalyst is activated to obtain an activated carbon black loaded with the metal catalyst.
[0079] In the application, the second protective gas may include N 2 , He, Ne and Ar, etc.
[0080] The reducing gas may include hydrogen (H 2 )wait.
[0081] S22. The activated carbon black loaded metal catalyst is transported into the reactor under the third protective gas, and in the first stage: the carbon source with a first gas flow rate, the nitrogen source with a second gas flow rate, and the fourth protective gas with a third gas flow rate are reacted at a fourth temperature for a fourth time; then, in the second stage: the carbon source with a fourth gas flow rate, the nitrogen source with a fifth gas flow rate, and the fifth protective gas with a sixth gas flow rate are reacted at a fifth temperature for a fifth time to obtain a composite powder with nitrogen-containing carbon nanotubes in situ grown on the surface of the carbon black.
[0082] The first gas flow rate is lower than the fourth gas flow rate, the second gas flow rate is higher than the fifth gas flow rate, and the fourth temperature is higher than the fifth temperature.
[0083] In applications, the carbon source may include cyclohexanone, cyclohexane, etc. The carbon source is a raw material for growing carbon nanotubes, and the carbon source is more conducive to the addition of nitrogen.
[0084] The nitrogen source may include ammonia (NH 3 ) etc. In the first stage, the proportion of nitrogen source is relatively large, and the reaction temperature in the first stage is relatively high, so that the nitrogen element can be quickly inserted into the defects and other positions in the process of carbon source generating carbon nanotubes, that is, nitrogen-containing carbon nanotubes are generated; then, in the second stage, the proportion of nitrogen source is reduced, and the reaction temperature is slightly lowered, and nitridation is reduced, so that carbon nanotubes can be uniformly and stably grown in situ on the surface of carbon black, and the carbon nanotubes are evenly arranged on the surface of carbon black.
[0085] The third protective gas may be an inert gas atmosphere, and the inert gas may be nitrogen (N 2 ), helium (He), neon (Ne) and argon (Ar), etc.
[0086] The fourth protective gas may be an inert gas atmosphere, and the inert gas may be nitrogen (N 2 ), helium (He), neon (Ne) and argon (Ar), etc.
[0087] The fifth protective gas may be an inert gas atmosphere, and the inert gas may be nitrogen (N 2 ), helium (He), neon (Ne) and argon (Ar), etc.
[0088] It should be noted that the third protective gas, the fourth protective gas and the fifth protective gas can be the same, which is simple and easy to implement.
[0089] In addition, the nitrogen source can be introduced after the reaction has grown for a period of time, that is, after a small section of carbon nanotubes has grown on the surface of the carbon black. In this way, when the carbon-oxygen bond in the carbon source is broken, the surface oxidation effect of oxygen on the metal catalyst can be reduced.
[0090] Metal catalysts can effectively catalyze and promote the activation reaction, improve reaction efficiency and selectivity, and make the carbon source generate hexagonal rings to form carbon nanotubes. The carbon nanotubes grow on the surface of carbon black. During this process, the nitrogen source can be inserted into some defects in the hexagonal rings generated by the carbon source, that is, nitrogen-containing carbon nanotubes are generated on the surface of carbon black. While the carbon black and the carbon nanotubes are chemically combined, the nitrogen element makes them more conductive.
[0091] S23. The composite powder with nitrogen-containing carbon nanotubes in situ grown on the surface of carbon black is acid-washed and impurities-removed to obtain carbon nanotube-modified carbon black conductive powder.
[0092] In the application, the above pickling can use HCl, H 2 SO 4 Wait for cleaning.
[0093] The specific preparation method of carbon nanotube modified carbon black conductive powder is given below, and the preparation method comprises the following steps:
[0094] (1) Add the carbon black loaded with metal catalyst into the reduction activation device and introduce 100-150L / min of H 2 and N 2 (H 2 With N 2 The volume ratio of the catalyst is 1:1-2:1), and the catalyst is reduced at a reduction temperature of 600-700° C. for 5-10 min to obtain an activated carbon black-supported metal catalyst.
[0095] (2) Using continuous input or pulse input, the activated carbon black loaded metal catalyst is transported into the reactor with an inert gas. In the first stage, a carbon source with a gas flow rate of 400-500 L / min, a nitrogen source with a gas flow rate of 80-150 L / min, and an inert gas with a gas flow rate of 550-650 L / min are used to react at a temperature of 660-700°C for 8-15 minutes. Then, in the second stage, a carbon source with a gas flow rate of 500-600 L / min, a nitrogen source with a gas flow rate of 30-50 L / min, and an inert gas with a gas flow rate of 550-650 L / min are used to react at a temperature range of 600-650°C for 30-40 minutes to obtain a composite powder with nitrogen-containing carbon nanotubes in situ grown on the carbon black surface.
[0096] (3) The composite powder with nitrogen-containing carbon nanotubes grown in situ on the carbon black surface is acid-washed and impurity-removed to obtain carbon nanotube-modified carbon black conductive powder.
[0097] The preparation method of carbon nanotube modified carbon black high conductivity powder provided in the embodiment of the present application, on the one hand, adopts high temperature and pressure impregnation to load the carbon black with metal catalyst. The high temperature and pressure of this process accelerate the diffusion rate of the active component, so that the metal catalyst is evenly dispersed on the surface of the carbon black, and the loading amount and uniformity of the metal catalyst loaded on the carbon black are improved; on the other hand, the metal catalyst in the carbon black loaded with the metal catalyst is calcined and then reduced and activated, which can enhance the catalytic activity of the metal catalyst and is beneficial to the subsequent generation of carbon nanotubes; on the other hand, carbon nanotubes are generated in multiple stages in a reactor, so that the nitrogen source can be inserted into the defects in the carbon hexagonal ring and other positions, and nitrogen-containing carbon nanotubes are grown in situ on the surface of the carbon black, so as to achieve chemical bonding between the carbon black and the carbon nanotubes and enhance the conductivity of the carbon nanotube modified carbon black high conductivity powder.
[0098] In summary, by optimizing the carbon black loading metal catalyst process, the carbon nanotube growth process, etc., nitrogen-containing carbon nanotubes can be uniformly grown on the surface of carbon black. When the carbon nanotube-modified carbon black high-conductivity powder is used as a conductive agent, a conductive path can be obtained with a small amount of use, especially the nitrogen source also improves the conductivity, which inevitably reduces the amount of carbon black, so that it can be directly added to the system in the form of powder when used as a conductive agent, and it is very easy to disperse into various systems, which is simple and easy to achieve.
[0099] In the second aspect, based on the above-mentioned preparation process of carbon nanotube-modified carbon black conductive powder, an embodiment of the present application provides a carbon nanotube-modified carbon black conductive powder, which includes: carbon black and nitrogen-containing carbon nanotubes, and the nitrogen-containing carbon nanotubes are in-situ grown on the surface of the carbon black.
[0100] The weight ratio of carbon black to nitrogen-containing carbon nanotubes can be in the range of 10: 1-3: 1. Thus, using a small amount of nitrogen-containing carbon nanotubes can significantly improve the conductivity of carbon black and significantly reduce the amount of carbon black used.
[0101] The oil absorption of the carbon nanotube modified carbon black conductive powder can range from 210 to 280 ml / 100 g. For example, the oil absorption of the carbon nanotube modified carbon black conductive powder can be 210 ml / 100 g, 220 ml / 100 g, 230 ml / 100 g, 240 ml / 100 g, 260 ml / 100 g or 280 ml / 100 g, etc. Therefore, the carbon nanotube modified carbon black conductive powder has good wettability, so that it can be better dispersed in other systems, thereby improving the dispersibility of the carbon nanotube modified carbon black conductive powder.
[0102] The resistivity of the carbon nanotube-modified carbon black conductive powder can range from 50 to 90 mΩ·cm. For example, the resistivity of the carbon nanotube-modified carbon black conductive powder can be 50 mΩ·cm, 60 mΩ·cm, 70 mΩ·cm, 80 mΩ·cm, 85 mΩ·cm or 90 mΩ·cm, etc. Therefore, the carbon nanotube-modified carbon black conductive powder has good conductivity.
[0103] The specific surface area of carbon black conductive powder modified by carbon nanotubes can range from 110 to 180 m 2 / g, for example, the resistivity of the carbon nanotube modified carbon black conductive powder can be 110m 2 / g, 130m 2 / g, 150m 2 / g, 160m 2 / g, 170m 2 / g or 180m 2 / g, etc. Therefore, the specific surface area of carbon black conductive powder modified by carbon nanotubes is smaller and the dispersion performance is better.
[0104] It should be noted that the carbon black, nitrogen-containing carbon nanotubes, etc. in the embodiments of the present application can refer to the above embodiments and will not be described in detail here.
[0105] The following uses a number of specific embodiments to illustrate the preparation methods and applications of the conductive powders provided in the embodiments and comparative examples of the present application.
[0106] 1. Embodiments of the carbon nanotube-modified carbon black conductive powder and preparation method thereof of the present application:
[0107] Example 1
[0108] 1. Carbon black loaded metal catalyst:
[0109] (1). Selection and pretreatment of carbon black:
[0110] Select N326 with a powder particle size of 100-20000nm and a resistivity of 0.2Ω·cm, place N326 in concentrated HCl with a molar concentration of 0.7mol / L, pretreat at 70°C for 1h, filter and wash until the filtrate is neutral, and then dry at 110°C for 19h to obtain carbon black purified by concentrated HCl.
[0111] (2) Preparation of Fe(NO 3 ) 3 Solution.
[0112] (3) Preparation of carbon black loaded with metal catalyst:
[0113] Will Fe(NO 3 ) 3 solution, carbon black purified by concentrated HCl, and citric acid in H 2 O, heated to 100 °C, maintained at 0.1 MPa, immersed for 0.5 h to obtain a catalyst precursor, and then placed in a muffle furnace under N 2 and calcined at 450° C. for 2 h. After cooling, the mixture was sieved using an 80-mesh sieve to obtain carbon black loaded with a metal catalyst.
[0114] Among them, carbon black purified by concentrated HCl, citric acid, Fe(NO 3 ) 3 Fe(NO 3 ) 3 The weight ratio is 1.2:1.05:0.8.
[0115] 2. Preparation of carbon nanotube modified carbon black conductive powder:
[0116] (1) Add the carbon black loaded with metal catalyst into the reduction activation device and introduce 100 L / min of H 2 and N2 , reduced at a reduction temperature of 600°C for 5 minutes.
[0117] Among them, H 2 With N 2 The volume ratio is 1:1.
[0118] (2) Use continuous input or pulse input, with N 2 The carbon black loaded with metal catalyst was transported to the reactor. In the first stage, cyclohexanone with a gas flow rate of 400 L / min, ammonia with a gas flow rate of 80 L / min, and N with a gas flow rate of 550 L / min were used. 2 , reacted at 660°C for 8 min; then, in the second stage: cyclohexanone with a gas flow rate of 500 L / min, ammonia with a gas flow rate of 30 L / min, and N 2 , reacting at a temperature range of 600°C for 30 minutes to obtain a composite powder with nitrogen-containing carbon nanotubes in situ grown on the carbon black surface.
[0119] (3) The composite powder with nitrogen-containing carbon nanotubes grown in situ on the carbon black surface is washed with HCl to remove impurities, thereby obtaining carbon nanotube-modified carbon black conductive powder.
[0120] Example 2
[0121] 1. Carbon black loaded metal catalyst:
[0122] (1). Selection and pretreatment of carbon black:
[0123] Select N326 with a powder particle size of 100-20000nm and a resistivity of 1Ω·cm, and place N326 in a concentrated H solution with a molar concentration of 0.8mol / L. 2 SO 4 The mixture was pretreated at 80 °C for 1.5 h, filtered and washed until the filtrate was neutral, and then dried at 115 °C for 20 h to obtain concentrated H 2 SO 4 Purified carbon black.
[0124] (2) Preparation of FeCl 2 Solution.
[0125] (3) Preparation of carbon black loaded with metal catalyst:
[0126] FeCl 2 solution, carbon black purified by concentrated HCl and tartaric acid in H 2O, heat to 150°C, maintain pressure at 0.15 MPa and immerse for 1 hour to obtain a catalyst precursor, then place the catalyst precursor in a muffle furnace, calcine at He and 480°C for 3 hours, and sieve with a 85-mesh screen after cooling to obtain carbon black loaded with a metal catalyst.
[0127] Among them, carbon black purified by concentrated HCl, tartaric acid, FeCl 2 FeCl in solution 2 The weight ratio is 1.25:1.08:0.9.
[0128] 2. Preparation of carbon nanotube modified carbon black conductive powder:
[0129] (1) Add the carbon black loaded with metal catalyst into the reduction activation device and introduce 110 L / min of H 2 and N 2 , reduced at a reduction temperature of 620°C for 6 min.
[0130] Among them, H 2 With N 2 The volume ratio is 1.2:1.
[0131] (2) Using continuous input or pulse input, the carbon black loaded with the metal catalyst is transported into the reactor with He. In the first stage, cyclohexane with a gas flow rate of 420 L / min, ammonia with a gas flow rate of 90 L / min, and He with a gas flow rate of 580 L / min are used to react at a temperature of 670°C for 9 minutes. Then, in the second stage, cyclohexane with a gas flow rate of 520 L / min, ammonia with a gas flow rate of 35 L / min, and He with a gas flow rate of 580 L / min are used to react at a temperature range of 610°C for 32 minutes to obtain a composite powder with nitrogen-containing carbon nanotubes in situ grown on the surface of the carbon black.
[0132] (3) The composite powder with nitrogen-containing carbon nanotubes grown in situ on the carbon black surface is washed with HCl to remove impurities, thereby obtaining carbon nanotube-modified carbon black conductive powder.
[0133] Example 3
[0134] 1. Carbon black loaded metal catalyst:
[0135] (1). Selection and pretreatment of carbon black:
[0136] Select N326 with a particle size of 100-20000nm and a resistivity of 10Ω·cm, and place N326 in a concentrated H solution with a molar concentration of 0.9mol / L. 3 PO 4The mixture was pretreated at 85 °C for 2 h, filtered and washed until the filtrate was neutral, and then dried at 120 °C for 21 h to obtain concentrated H 3 PO 4 Purified carbon black.
[0137] (2) Preparation of CoCl 2 Solution.
[0138] (3) Preparation of carbon black loaded with metal catalyst:
[0139] CoCl 2 solution, carbon black purified by concentrated HCl, and sorbic acid in H 2 O, heat to 200°C, maintain pressure at 0.2 MPa and immerse for 1.5 hours to obtain a catalyst precursor, then place the catalyst precursor in a muffle furnace, calcine at Ne and 500°C for 4 hours, and sieve with a 90-mesh sieve after cooling to obtain carbon black loaded with a metal catalyst.
[0140] Among them, carbon black, sorbic acid, CoCl 2 CoCl in solution 2 The weight ratio is 1.3:1.1:1.0.
[0141] 2. Preparation of carbon nanotube modified carbon black conductive powder:
[0142] (1) Add the carbon black loaded with metal catalyst into the reduction activation device and introduce 120L / min of H 2 and N 2 , reduced at a reduction temperature of 640°C for 7 minutes.
[0143] Among them, H 2 With N 2 The volume ratio is 1.4:1.
[0144] (2) Using continuous input or pulse input, Ne is used to transport the carbon black loaded with the metal catalyst into the reactor. In the first stage, cyclohexanone with a gas flow rate of 440 L / min, ammonia with a gas flow rate of 100 L / min, and Ne with a gas flow rate of 600 L / min are used to react at a temperature of 680°C for 10 minutes. Then, in the second stage, cyclohexanone with a gas flow rate of 540 L / min, ammonia with a gas flow rate of 40 L / min, and Ne with a gas flow rate of 600 L / min are used to react at a temperature range of 620°C for 34 minutes to obtain a composite powder with nitrogen-containing carbon nanotubes in situ grown on the surface of the carbon black.
[0145] (3) The composite powder with nitrogen-containing carbon nanotubes grown in situ on the carbon black surface is washed with HCl to remove impurities, thereby obtaining carbon nanotube-modified carbon black conductive powder.
[0146] Example 4
[0147] 1. Carbon black loaded metal catalyst:
[0148] (1). Selection and pretreatment of carbon black:
[0149] Select N326 with a powder particle size of 100-20000nm and a resistivity of 20Ω·cm, place N326 in concentrated HCl with a molar concentration of 1.0 mol / L, pretreat at 90°C for 2.5h, filter and wash until the filtrate is neutral, and then dry at 123°C for 22h to obtain carbon black purified by concentrated HCl.
[0150] (2) Preparation of CoSO 4 Solution.
[0151] (3) Preparation of carbon black loaded with metal catalyst:
[0152] CoSO 4 solution, carbon black purified by concentrated HCl and EDTA in H 2 O, heat to 250°C, maintain pressure at 0.25 MPa and immerse for 2 hours to obtain a catalyst precursor, then place the catalyst precursor in a muffle furnace, calcine at Ar and 550°C for 5 hours, and sieve with a 95-mesh sieve after cooling to obtain carbon black loaded with a metal catalyst.
[0153] Among them, carbon black purified by concentrated HCl, EDTA, CoSO 4 CoSO in solution 4 The weight ratio is 1.35:1.15:1.0.
[0154] 2. Preparation of carbon nanotube modified carbon black conductive powder:
[0155] (1) Add the carbon black loaded with metal catalyst into the reduction activation device and introduce 130L / min of H 2 and N 2 , reduced at a reduction temperature of 660°C for 8 min.
[0156] Among them, H 2 With N 2 The volume ratio is 1.6:1.
[0157] (2) Using continuous input or pulse input, the carbon black loaded with the metal catalyst is transported into the reactor with Ar. In the first stage, cyclohexane with a gas flow rate of 460 L / min, ammonia with a gas flow rate of 120 L / min, and Ar with a gas flow rate of 620 L / min are used to react at a temperature of 685°C for 12 minutes. Then, in the second stage, cyclohexane with a gas flow rate of 560 L / min, ammonia with a gas flow rate of 42 L / min, and Ar with a gas flow rate of 620 L / min are used to react at a temperature range of 630°C for 36 minutes to obtain a composite powder with nitrogen-containing carbon nanotubes in situ grown on the surface of the carbon black.
[0158] (3) The composite powder with nitrogen-containing carbon nanotubes grown in situ on the carbon black surface is washed with HCl to remove impurities, thereby obtaining carbon nanotube-modified carbon black conductive powder.
[0159] Example 5
[0160] 1. Carbon black loaded metal catalyst:
[0161] (1). Selection and pretreatment of carbon black:
[0162] Select N326 with a particle size of 100-20000nm and a resistivity of 30Ω·cm, and place N326 in a concentrated H solution with a molar concentration of 1.1 mol / L. 2 SO 4 The mixture was pretreated at 95 °C for 2.8 h, filtered and washed until the filtrate was neutral, and then dried at 128 °C for 23 h to obtain concentrated H 2 SO 4 Purified carbon black.
[0163] (2) Preparation of Ni(NO 3 ) 2 Solution.
[0164] (3) Preparation of carbon black loaded with metal catalyst:
[0165] Will Ni(NO 3 ) 2 solution, carbon black purified by concentrated HCl, and ethylene glycol in H 2 O, and heated to 280°C. The catalyst precursor was obtained by immersing the catalyst in a muffle furnace under N 2 and calcined at 580° C. for 6 h. After cooling, the mixture was sieved using a 98-mesh sieve to obtain carbon black loaded with a metal catalyst.
[0166] Among them, carbon black, ethylene glycol, Ni(NO 3 ) 2 Ni(NO3 ) 2 The weight ratio is 1.4:1.18:1.1.
[0167] 2. Preparation of carbon nanotube modified carbon black conductive powder:
[0168] (1) Add the carbon black loaded with metal catalyst into the reduction activation device and introduce 140L / min of H 2 and N 2 , reduced at a reduction temperature of 680°C for 9 minutes.
[0169] Among them, H 2 With N 2 The volume ratio is 1.8:1.
[0170] (2) Use continuous input or pulse input, with N 2 The carbon black loaded with metal catalyst was transported to the reactor. In the first stage, cyclohexanone with a gas flow rate of 480 L / min, ammonia with a gas flow rate of 140 L / min, and N with a gas flow rate of 640 L / min were used. 2 , reacted at 690°C for 14 min; then, in the second stage: cyclohexanone at a gas flow rate of 580 L / min, ammonia at a gas flow rate of 48 L / min, and N at a gas flow rate of 640 L / min 2 , reacting at a temperature range of 640°C for 38 minutes to obtain a composite powder with nitrogen-containing carbon nanotubes in situ grown on the carbon black surface.
[0171] (3) The composite powder with nitrogen-containing carbon nanotubes grown in situ on the carbon black surface is washed with HCl to remove impurities, thereby obtaining carbon nanotube-modified carbon black conductive powder.
[0172] Example 6
[0173] 1. Carbon black loaded metal catalyst:
[0174] Select N326 with a particle size of 100-20000nm and a resistivity of 50Ω·cm, and place N326 in a concentrated H solution with a molar concentration of 1.2mol / L. 3 PO 4 The product was pretreated at 100 °C for 3 h, filtered and washed until the filtrate was neutral, and then dried at 130 °C for 24 h to obtain concentrated H 3 PO 4 Purified carbon black.
[0175] (2) Preparation of Co 2 Fe 2 O 5 Solution.
[0176] (3) Preparation of carbon black loaded with metal catalyst:
[0177] Co 2 Fe 2 O 5 solution, carbon black purified by concentrated HCl, and polyethylene glycol in H 2 O, heated to 300 ° C, maintained at 0.4 MPa, and immersed for 3 h to obtain a catalyst precursor, and then placed the catalyst precursor in a muffle furnace under N 2 and calcined at 620° C. for 7 h. After cooling, the mixture was sieved using a 100-mesh sieve to obtain carbon black loaded with a metal catalyst.
[0178] Among them, carbon black purified by concentrated HCl, polyethylene glycol, Co 2 Fe 2 O 5 Co in solution 2 Fe 2 O 5 The weight ratio is 1.5:1.2:1.2.
[0179] 2. Preparation of carbon nanotube modified carbon black conductive powder:
[0180] (1) Add the carbon black loaded with metal catalyst into the reduction activation device and introduce 150L / min of H 2 and N 2 , reduced at a reduction temperature of 700°C for 10 min.
[0181] Among them, H 2 With N 2 The volume ratio is 2:1.
[0182] (2) Use continuous input or pulse input, with N 2 The carbon black loaded with metal catalyst was transported to the reactor. In the first stage, cyclohexane with a gas flow rate of 500 L / min, ammonia with a gas flow rate of 150 L / min, and N with a gas flow rate of 650 L / min were used. 2 , reacted at 700 ° C for 15 min; then, in the second stage: cyclohexane with a gas flow rate of 600 L / min, ammonia with a gas flow rate of 50 L / min, and N 2 , reacting at a temperature range of 650°C for 40 minutes to obtain a composite powder with nitrogen-containing carbon nanotubes in situ grown on the carbon black surface.
[0183] (3) The composite powder with nitrogen-containing carbon nanotubes grown in situ on the carbon black surface is washed with HCl to remove impurities, thereby obtaining carbon nanotube-modified carbon black conductive powder.
[0184] 2. Comparative Example Conductive powder and preparation method thereof:
[0185] Comparative Example 1
[0186] Compared with Example 1, the main difference is that the process of growing carbon nanotubes is not carried out in stages, as follows:
[0187] 2. Preparation of carbon nanotube modified carbon black conductive powder:
[0188] (2) Use continuous input or pulse input, with N 2 The carbon black loaded with metal catalyst was transported into the reactor, and cyclohexane with a gas flow rate of 500 L / min, ammonia with a gas flow rate of 40 L / min, and N with a gas flow rate of 550 L / min were used. 2 , reacting at a temperature of 660°C for 40 minutes to obtain a composite powder with nitrogen-containing carbon nanotubes in situ grown on the carbon black surface.
[0189] Comparative Example 2
[0190] Compared with Example 1, N326 carbon black of the same specification is directly mixed with carbon nanotubes without in-situ growth.
[0191] A lithium ion battery using the carbon nanotube-modified carbon black conductive powder of the embodiment of the present application is provided below:
[0192] 1. Preparation of negative electrode sheet:
[0193] The negative electrode ingredients were prepared according to the mass ratio of silicon oxide (SiO), carboxymethyl cellulose (CMC), polyacrylic acid (PAA), and conductive powder of 97.4:1.6:0.5:0.5, and deionized water was added to adjust the solid content to 35wt%, and then put into a double planetary mixer for vacuum high-speed homogenization. The revolution speed was adjusted to 2000RPM and the rotation speed was 800RPM. After homogenization for 20 minutes, it was coated on the negative electrode collector and dried at 80°C to obtain the negative electrode sheet. The test results are shown in Table 1.
[0194] 2.Battery assembly and testing
[0195] The negative electrode sheet was cut to serve as the negative electrode, and the positive electrode was made of lithium cobalt oxide to prepare a CR2032 button battery, which was tested on a Blue Electric test system.
[0196] The charge and discharge conditions were set as follows: charge to a cut-off voltage of 1.5 V, discharge to a cut-off voltage of 0.005 V, cycle at 0.1 C for 5 weeks, and cycle at 1 C for 100 weeks, to obtain the 0.1 C charge capacity, 1 C charge capacity, and 1 C cycle retention rate for 100 weeks of the CR2032 button battery. The test results are shown in Table 1.
[0197] Table 1
[0198]
[0199] As can be seen from Table 1, compared with Comparative Example 1, the process of growing carbon nanotubes in Example 1 of the present application is not carried out in stages, which reduces the content of nitrogen doped carbon nanotubes, and at the same time leads to a decrease in the density of carbon nanotubes grown on the surface of carbon black, resulting in a decrease in the overall conductivity of the conductive powder. As a result, the sheet resistance of the negative electrode plate is high, the battery's 0.1C charging capacity, 1C charging and 1C cycle 100-week retention rate capacity are all low, and the lithium-ion battery has a short service life and poor effect.
[0200] Compared with Example 2, Example 1 of the present application directly mixes N326 carbon black of the same specification with carbon nanotubes in Example 2, and the carbon nanotubes do not grow in situ on the surface of the carbon black, resulting in the inability of carbon black and carbon nanotubes to form an effective combination, and only a simple mixture, and the inability to form a good conductive path between the two, resulting in poor dispersion performance, resulting in a decrease in the overall conductivity of the conductive powder. As a result, the sheet resistance of the negative electrode sheet is high, the battery's 0.1C charging capacity, 1C charging and 1C cycle 100-week retention rate capacity are all low, and the lithium-ion battery has a short service life and poor effect.
[0201] Compared with Example 1, Examples 2-6 of the present application are only slightly different in the formula of the carbon nanotube modified carbon black conductive powder and some parameters in the process. Therefore, compared with Comparative Examples 1-2, Examples 2-6 can make the modified carbon black react well with the carbon nanotubes as much as possible, and the modified carbon black and carbon nanotubes can form a good conductive path, and the amount of carbon black can be reduced. The dispersion of carbon nanotubes is better, and the overall conductive performance of the carbon nanotube modified carbon black conductive powder is significantly improved. Therefore, the sheet resistance of the negative electrode plate is low, the battery's 0.1C charging capacity, 1C charging and 1C cycle 100-week retention rate capacity are all high, and the lithium-ion battery has a long service life and good effect.
[0202] Only the contents related to the invention are introduced here. The rest can be obtained by referring to the relevant technology and will not be described in detail here.
[0203] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A carbon nanotube modified carbon black conductive powder, characterized in that: include: Carbon black and nitrogen-containing carbon nanotubes, wherein the nitrogen-containing carbon nanotubes are in-situ grown on the surface of the carbon black; the weight ratio of the carbon black to the nitrogen-containing carbon nanotubes is in the range of 10:1-3:1; The oil absorption range of the carbon nanotube modified carbon black conductive powder is 210-280 ml / 100 g; and / or, The resistivity of the carbon nanotube-modified carbon black conductive powder is in the range of 50-90 mΩ·cm; and / or, The specific surface area of the carbon nanotube modified carbon black conductive powder is in the range of 110-180 m 2 / g.
2. The carbon nanotube-modified carbon black conductive powder according to claim 1, characterized in that: The carbon nanotube modified carbon black conductive powder is obtained by the following steps: Step 1. Carbon black supports metal catalyst; Step 2. In-situ growth of carbon nanotubes on the surface of the carbon black loaded with the metal catalyst and treatment to form the carbon nanotube-modified carbon black conductive powder; The in-situ growth of carbon nanotubes on the surface of carbon black loaded with a metal catalyst is carried out in two stages: in the first stage, the carbon black loaded with a metal catalyst is reacted in a carbon source with a first gas flow rate, a nitrogen source with a second gas flow rate, and a fourth protective gas with a third gas flow rate at a fourth temperature for a fourth time; in the second stage, the carbon source with a fourth gas flow rate, a nitrogen source with a fifth gas flow rate, and a fifth protective gas with a sixth gas flow rate are reacted at a fifth temperature for a fifth time to form a composite powder with nitrogen-containing carbon nanotubes in situ grown on the surface of the carbon black; wherein the first gas flow rate is less than the fourth gas flow rate, the second gas flow rate is greater than the fifth gas flow rate, and the fourth temperature is greater than the fifth temperature.
3. The carbon nanotube-modified carbon black conductive powder according to claim 2, characterized in that: After the step 1. of loading the metal catalyst on the carbon black and before the step 2. of in-situ growing carbon nanotubes on the surface of the carbon black loaded with the metal catalyst and treating the carbon nanotubes to form the carbon nanotube-modified carbon black conductive powder, the following steps are also included: Step 1.
5. Activating the metal catalyst; The activation treatment of the metal catalyst includes: reducing the carbon black loaded with the metal catalyst in hydrogen and nitrogen with a gas flow rate range of 100-150 L / min and a temperature of 600-700° C. for 5-10 minutes to form an activated carbon black loaded with metal catalyst; wherein hydrogen is used as a reducing gas and nitrogen is used as a protective gas.
4. The carbon nanotube-modified carbon black conductive powder according to claim 3, characterized in that: The volume ratio of hydrogen to nitrogen ranges from 1:1 to 2:
1.
5. The carbon nanotube-modified carbon black conductive powder according to claim 3, characterized in that: The in-situ growth of carbon nanotubes on the surface of carbon black loaded with a metal catalyst is carried out in two stages: in the first stage, the carbon black loaded with a metal catalyst is reacted in a carbon source with a first gas flow rate, a nitrogen source with a second gas flow rate, and a fourth protective gas with a third gas flow rate at a fourth temperature for a fourth time; in the second stage, the carbon source with a fourth gas flow rate, a nitrogen source with a fifth gas flow rate, and a fifth protective gas with a sixth gas flow rate are reacted at a fifth temperature for a fifth time to form a composite powder with in-situ growth of nitrogen-containing carbon nanotubes on the surface of carbon black, including: The activated carbon black loaded with a metal catalyst is transported to a reaction furnace by a first inert gas. In the first stage, a carbon source with a gas flow rate in the range of 400-500 L / min, a nitrogen source with a gas flow rate in the range of 80-150 L / min, and a second inert gas with a gas flow rate in the range of 550-650 L / min are used to react at a temperature of 660-700°C for 8-15 minutes. In the second stage, a carbon source with a gas flow rate in the range of 500-600 L / min, a nitrogen source with a gas flow rate in the range of 30-50 L / min, and a third inert gas with a gas flow rate in the range of 550-650 L / min are used to react at a temperature range of 600-650°C for 30-40 minutes to obtain a composite powder with nitrogen-containing carbon nanotubes in situ grown on the surface of the carbon black.
6. The carbon nanotube-modified carbon black conductive powder according to claim 2, characterized in that: The steps of the carbon black-loaded metal catalyst are as follows: The conductive carbon black is subjected to acid treatment and drying to obtain the carbon black subjected to acid purification; The metal salt solution, the carbon black purified by the acid solution and the complexing agent are mixed and treated to obtain the carbon black loaded with the metal catalyst.
7. The carbon nanotube-modified carbon black conductive powder according to claim 6, characterized in that: The method of acidifying and drying the conductive carbon black to obtain the acid-purified carbon black comprises: Conductive carbon black with a powder particle size range of 100-20000nm and a resistivity range of 0.2-50Ω·cm is placed in an acid solution with a molar concentration range of 0.7-1.2mol / L, pretreated at a temperature of 70-100°C for 1-3h, filtered and washed until the filtrate is neutral, and then dried at a temperature of 110-130°C for 19-24h to obtain the carbon black purified by the acid solution.
8. The carbon nanotube-modified carbon black conductive powder according to claim 6, characterized in that: The metal salt solution, the carbon black purified by the acid solution and the complexing agent are mixed and treated to obtain the carbon black loaded with the metal catalyst, which comprises: The metal salt solution, the carbon black purified by the acid solution and the complexing agent are mixed, heated to 100-300°C, maintained at a pressure of 0.1-0.4MPa, and immersed for 0.5-3h to obtain a catalyst precursor, and then the catalyst precursor is placed in a muffle furnace, calcined for 2-7h in a first protective atmosphere at a temperature of 450-620°C, and sieved with a sieve of 80-100 mesh after cooling to obtain the carbon black loaded with the metal catalyst.
9. The carbon nanotube-modified carbon black conductive powder according to any one of claims 6 to 8, characterized in that: The weight ratio of the carbon black purified by acid solution, the complexing agent, and the metal salt in the metal salt solution is in the range of 1.2-1.5:1.05-1.2:0.8-1.
2.
10. A lithium ion battery, characterized in that: The invention comprises the carbon nanotube-modified carbon black conductive powder as claimed in any one of claims 1 to 9.
Citation Information
Cited By
Carbon nanotube / graphene composite conductive agent and preparation method thereof
CN121546070A
Carbon nanotube / graphene composite conductive agent and preparation method thereof
CN121546070B